Glutamate Receptor-Mediated Neurotoxicity in a Model of Ethanol Dependence and Withdrawal in Rat Organotypic Hippocampal Slice Cultures - Gerace, Elisabetta; Landucci, Elisa; Bani, Daniele; Moroni, Flavio; Mannaioni, Guido; Pellegrini-Giampietro, Domenico E. (Frontiers in Neuroscience, 2019)
Long-term alcohol use can lead to alterations in brain structure and functions and, in some cases, to neurodegeneration. Several mechanisms have been proposed to explain ethanol (EtOH)-related brain injury. One of the most relevant mechanisms of alcohol-induced neurodegeneration involves glutamatergic transmission, but their exact role is not yet fully understood. We investigated the neurochemical mechanisms underlying the toxicity induced by EtOH dependence and/or withdrawal by exposing rat organotypic hippocampal slices to EtOH (100-300 mM) for 7 d and then incubating the slices in EtOH-free medium for the subsequent 24 h. EtOH withdrawal led to a dose-dependent CA1 pyramidal cell injury, as detected with propidium iodide fluorescence. Electron microscopy of hippocampal slices revealed that not only EtOH withdrawal but also 7 d chronic EtOH exposure elicited signs of apoptotic cell death in CA1 pyramidal cells. These data were supported by electrophysiological recordings of spontaneus Excitatory Post Synaptic Currents (sEPSCs) from CA1 pyramidal cells. The average amplitude of sEPSCs in slices treated with EtOH for 7 d was significantly increased, and even more so during the first 30 min of EtOH withdrawal, suggesting that the initial phase of the neurodegenerative process could be due to an excitotoxic mechanism. We then analyzed the expression levels of presynaptic (vGlut1, vGlut2, CB1 receptor, synaptophysin) and postsynaptic (PSD95, GluN1, GluN2A, GluN2B, GluA1, GluA2, mGluR1 and mGluR5) proteins after 7 d EtOH incubation or after EtOH withdrawal. We found that only GluA1 and mGluR5 expression levels were significantly increased after EtOH withdrawal and, in neuroprotection experiments, we observed that AMPA and mGluR5 antagonists attenuated EtOH withdrawal-induced toxicity. These data suggest that chronic EtOH treatment promotes abnormal synaptic transmission that may lead to CA1 pyramidal cell death after EtOH withdrawal through glutamate receptors and increased excitotoxicity.